Chicken Wastewater Treatment Using Carbon Filtration - ROSDAN, AMMAR NURHAKIM (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Water is one of a main sources for human and ecosystem. Water pollution nearby chicken slaughter house are in great concern towards housing area. This is very worrying especially during this uneven climate change in Malaysia. The after effect from raining and sudden bright sun can resulting a pungent smell occurs from the drainage system. This odor from the chicken wastewater may resulting toward environmental damage. This is because of the Fat, Oil and Grease (FOG) released from the chicken wastewater. The purpose of this study is to filtrate and improve the quality of the wastewater that disposed directly by the chicken slaughtering houses. The main material for this filtration system will be carbon powder. The filtration system also consists of nature resources such as soil, sand and coconut fiber in which it can save costs and easy to obtain. Total Dissolves Solid (TDS) and pH value will be the main benchmark for this study. Total dissolve solid will define on the safeness to be consume by human body while pH value will indicate the acidity and alkaline of the water. The range of pH that safe to be consume by human are from 6.5 to 8.5. The methodology used was using filtration system by combining soil, sand and coconut fiber as media filter of this filtration system. This method will reduce the TDS number and maintaining the pH value while decrease water pollution towards the environment. This method and material can improve the parameter such as reducing the TDS number and improving the pH value towards the chicken wastewater.